2020
DOI: 10.4251/wjgo.v12.i10.1195
|View full text |Cite
|
Sign up to set email alerts
|

Blood exosomal micro ribonucleic acid profiling reveals the complexity of hepatocellular carcinoma and identifies potential biomarkers for differential diagnosis

Abstract: BACKGROUND Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths worldwide, but there is a shortage of effective biomarkers for its diagnosis. AIM To explore blood exosomal micro ribonucleic acids (miRNAs) as potential biomarkers for HCC diagnosis. METHODS T RESULTS The principal component analysis suggested that daily alcohol consumption could alter the blood exosomal miRNA profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In addition, we searched and confirmed the target relationship between miR-455-5p and LRP4 by bioinformatics analysis and luciferase reporter assay. Functional analysis showed that cell proliferation, invasion, and migration were promoted by lowexpression of miR-455-5p in HCC cells, which is also consistent with former researches [ 29 , 44 ]. Under the regulation of miR-140-5p, LRP4 accelerated cell migration and invasion in gastric cancer [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we searched and confirmed the target relationship between miR-455-5p and LRP4 by bioinformatics analysis and luciferase reporter assay. Functional analysis showed that cell proliferation, invasion, and migration were promoted by lowexpression of miR-455-5p in HCC cells, which is also consistent with former researches [ 29 , 44 ]. Under the regulation of miR-140-5p, LRP4 accelerated cell migration and invasion in gastric cancer [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, the interesting finding was that the relatives and friends of Spanish MS patients have been more susceptible to COVID-19; the proportion is 32.7% in Spain, 14.2% in Cuba, and 0.52% in China, The possible reason could be widespread of COVID-19 in Spain. 27 Since Wuhan released from quarantine on April 8, the strict control of anti-epidemic measures by the Chinese government, there have been almost no other cases of MS with COVID-19 infection apart from sporadic cases in the past six months.…”
Section: Discussionmentioning
confidence: 99%
“…miR-30c-5p studied here has been shown to be involved in other cancers such as colorectal cancer [ 32 , 33 ], non-small cell lung cancer [ 34 , 35 ], gastric cancer [ 36 ], pancreatic ductal adenocarcinoma [ 37 ], renal cell carcinoma [ 38 , 39 ], hepatocellular carcinoma [ 40 , 41 , 42 , 43 ], breast cancer [ 44 , 45 , 46 , 47 , 48 ], laryngeal cancer [ 49 ], and other malignancies. For example, in gastric cancer, miR-30c-5p suppresses migration, invasion, and epithelial to mesenchymal transition via targeting MTA1 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%